Biomechanical Comparison of Different External Fixation Configurations for Posttraumatic Pelvic Ring Instability. (2nd February 2014) - Tiziani, Simon; Osterhoff, Georg; Ferguson, Stephen J.; Spreiter, Gregor; Scheyerer, Max J.; Spinas, Gian-Leza; Wanner, Guido A.; Simmen, Hans-Peter; Werner, Clément M. L.
Abstract : Background . External fixation is useful in the primary treatment of pelvic ring injuries. The present study compared the biomechanical stability of five different configurations of an external pelvic ring fixation system. Methods . Five configurations of an anterior external pelvic ring fixation system were tested using a universal testing machine. One single connecting rod was used in group "SINGLE, " two parallel connecting rods in group "DOUBLE, " two and four rods, respectively, in a tent-like configuration in groups "SINGLE TENT" and "DOUBLE TENT, " and a rhomboid-like configuration in group "RHOMBOID." Each specimen was subjected to a total of 2000 consecutive cyclic loadings at 1 Hz lateral compression/distraction (±50 N) and torque (±0.5 Nm) loading alternating every 200 cycles. Translational and rotational stiffness were determined at 100, 300, 500, 700, and 900 cycles. Results . The "SINGLE TENT" and "RHOMBOID" configurations already failed with a preloading of 50 N compression force. The "DOUBLE" configuration had around twice the translational stability compared with the "SINGLE" and "DOUBLE TENT" configurations. Rotational stiffness observed for the "DOUBLE" and "DOUBLE TENT" configurations was about 50% higher compared to the SINGLE configuration. Conclusion . Using two parallel connecting rods provides the highest translational and rotational stability.